PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN KOGNITIF SISWA PADA MATERI PERUBAHAN LINGKUNGAN DAN DAUR ULANG LIMBAH KELAS X DI SMA - Awalul Fatiqin; Amilda; Helen Monica Sari (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
This study aims to determine the Differences of Cognitive Ability of Students Before and After Application of Guided Inquiry Learning Model on Environmental Change Material and Waste Recycling Class X in SMA 'Aisyiyah 1 Palembang. The research method used in this research is weak experiment with one group pretest-posttest design. The population in this study consists of one class of 38 students. Sampling in this research using saturated sample technique because the entire population is sampled. Technique of collecting data is done with test question and observation sheet. Based on the results of data using t test at the real level of 5% tcount = 7,607 and ttable = 2.026, then tcount> ttable. This can be seen from the cognitive test of students showed sig thitung 0.000 <0,05, then Ha accepted and H0 rejected. The result of the analysis of the average increase of the students 'cognitive achievement on the pretest reaches 69.34 while the cognitive students in the posttest reach 83.82 means students' cognitive ability is higher after the application of guided inquiry learning model. Then it can be deduced that there is a Difference of Cognitive Ability of Students Before and After Application of Guided Inquiry Learning Model.